Effective In Vivo Topical Delivery of siRNA and Gene Silencing in Intact Corneal Epithelium Using a Modified Cell-Penetrating Peptide - Davide Schiroli; María J. Gómara; Eleonora Maurizi; Sarah D. Atkinson; Laura Mairs; Kathleen A. Christie; Diego F. Cobice; Cian M. McCrudden; M. Andrew Nesbit; Isabel Haro; Tara Moore (Elsevier, 2019)
Autosomal dominantly inherited genetic disorders such as corneal dystrophies are amenable to allele-specific gene silencing with small interfering RNA (siRNA). siRNA delivered to the cornea by injection, although effective, is not suitable for a frequent long-term treatment regimen, whereas topical delivery of siRNA to the cornea is hampered by the eye surface's protective mechanisms. Herein we describe an attractive and innovative alternative for topical application using cell-penetrating peptide derivatives capable of complexing siRNA non-covalently and delivering them into the cornea. Through a rational design approach, we modified derivatives of a cell-penetrating peptide, peptide for ocular delivery (POD), already proved to diffuse into the corneal layers. These POD derivatives were able to form siRNA-peptide complexes (polyplexes) of size and ζ-potential similar to those reported able to undergo cellular internalization. Successful cytoplasmic release and gene silencing in vitro was obtained when an endosomal disruptor, chloroquine, was added. A palmitoylated-POD, displaying the best delivery properties, was covalently functionalized with trifluoromethylquinoline, an analog of chloroquine. This modified POD, named trifluoromethylquinoline-palmitoyl-POD (QN-Palm-POD), when complexed with siRNA and topically applied to the eye in vivo, resulted in up to 30% knockdown of luciferase reporter gene expression in the corneal epithelium. The methods developed within represent a valid standardized approach that is ideal for screening of a range of delivery formulations. Keywords: siRNA, cornea, peptide, CPP, delivery